2001
DOI: 10.1161/01.hyp.38.3.692
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Hormones Modulate Endothelin-1 Vascular Reactivity and mRNA Expression in DOCA-Salt Hypertensive Rats

Abstract: Abstract-We previously demonstrated a differential activation of the endothelin-1 (ET-1) pathway in male and female deoxycorticosterone (DOCA)-salt hypertensive rats, with the male rats exhibiting marked alterations in vascular and pressor responses to ET-1 and Suc-[Glu, 9 Ala 11,15 ]-ET-1(8-21) (IRL-1620), an ET B agonist. Mechanisms underlying these gender differences are unclear, and we hypothesized that the ovarian hormones attenuate vascular ET B responses in female DOCA-salt rats. Female Wistar rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 27 publications
3
65
0
Order By: Relevance
“…Changes in ET Bmediated vascular responses were associated with increased ET-1 and ET B receptor gene expression in male, but not in female, animals (49). Furthermore, we observed that ovariectomy increases the vasoconstricting responses to the ET B agonist and that estrogen replacement therapy restores IRL-1620-induced responses, supporting our suggestion that the ovarian hormones modulate ET-1/ ET B receptor vascular responses/expression in DOCA-salt hypertension (50).…”
Section: Endothelinsupporting
confidence: 82%
“…Changes in ET Bmediated vascular responses were associated with increased ET-1 and ET B receptor gene expression in male, but not in female, animals (49). Furthermore, we observed that ovariectomy increases the vasoconstricting responses to the ET B agonist and that estrogen replacement therapy restores IRL-1620-induced responses, supporting our suggestion that the ovarian hormones modulate ET-1/ ET B receptor vascular responses/expression in DOCA-salt hypertension (50).…”
Section: Endothelinsupporting
confidence: 82%
“…21 In premenopausal women, a differential ratio of ET A to ET B receptors has also been found, favoring a vasodilator effect of endothelin via ET B receptors. 22 In recent animal studies, estradiol 23 or its metabolites 24 have been shown to inhibit endothelin synthesis and improve endothelial dysfunction in ovariectomized female spontaneously hypertensive rats 25 and DOCA-salt hypertensive rats. 23 Therefore, estrogens should be cardiovascular protective because of their positive effect on endothelin inhibition.…”
Section: Estrogen: "Good Girl"mentioning
confidence: 99%
“…Rat GAPDH was used as an internal control with a forward primer 5′ -CAC CAC CCT GTT GCT GTA-3′ and reverse primer 5′ -TAT GAT GAC ATC AAG AAG GTG G-3′ (David et al, 2001) to generate a 219-bp product.…”
Section: Rt-pcr Analysis Of Light Chain-ferritin (Lft) and Heavy Chaimentioning
confidence: 99%